Macroeconomic determinants of Islamic banking products in Indonesia - Nur Setyowati (Economies, 2019)
The purpose of the study was to investigate which factors determine saving and financing in Islamic banks in Indonesia by using Gregory-Hansen cointegration, vector error correction mode (VECM), Granger causality, and the impulse response function. The results disclose the existence of a long-running cointegrating relationship with a structural break in the deposit and financing case to the consumer price index, industrial production, interest rate, exchange rate, and Jakarta Islamic Index. Most of the structural breaks appeared in January 2006 and April 2007 for both deposit and financing, revealing the first stage of the financial crisis. Any short-term deviation between deposit and financing will give rise to a stable relationship in the long term. In the short-term, there is bidirectional causality between deposits and industrial production and between the consumer price index and financing. This finding shows that real activity, as measured by industrial production, is a highly determinant factor of Islamic bank deposits, while inflation, as measured by the customer price index, is the determinant factor of Islamic bank financing. Our results also suggest that a mix of dynamic behaviors from both Islamic bank savings and financing was revealed in response to the shock of the macroeconomic variable, giving better insight for the government and stakeholders into Indonesian Islamic banking.
Keywords: 330; Islamic bank; saving; financing; consumer price index; industrial production; interest rate; exchange rate; Jakarta Islamic index